Cone Beam Computed Tomography in Oral Cancer: A Scoping Review - Muhammad Aiman Mohd Nizar; Syed Nabil (Diagnostics)
Objectives: The present scoping review aims to explore and provide an overview of the current applications of cone beam computed tomography (CBCT) in the management of oral cancer. Methods: This study was conducted in accordance with the JBI Guidance for Scoping Reviews and reported following the PRISMA Extension for Scoping Reviews (PRISMA-ScR). A systematic search was performed across the following databases: PubMed, OVID, Scopus, Web of Science, and the Cochrane Library to answer the research question: “What are the current applications of CBCT in the perioperative management of patients with oral cancer?”. Results: A total of 52 studies met the inclusion criteria. Four major areas of CBCT application in oral cancer were identified: radiotherapy planning and monitoring (25 studies), assessment of bone invasion (16 studies), intraoperative surgical guidance (6 studies), and evaluation of treatment-related complications (5 studies). These findings highlight the diverse but focused use of CBCT across different stages of oral cancer management. Conclusions: CBCT is increasingly utilized in the perioperative management of oral cancer, with its application in radiotherapy planning and assessment being the most well-established. However, other uses, such as for surgical navigation and complication assessment, are still emerging, with promising evidence. Further research is needed to expand and validate these applications.